ANALISIS ZAT PEWARNA MERAH RHODAMIN B PADA GULA KAPAS DI KABUPATEN PASURUAN - Nisa, Manzila Fitrotun; Jayadi, Lukky; Fajar, Ibnu (Poltekkes Kemenkes Malang, 2022)
Rhodamine B is a synthetic dye that is used to dye textiles, but it is often misused to color a street food product such as cotton sugar. The short term effects of Rhodamin B if it comes in contact with the skin or eyes are irritation of the affected area, acute poisoning, abdominal pain, vomiting, diarrhea, headaches, dizziness and hypersalivation. While the long-term effects caused are irritation of the gastrointestinal tract, disorders of several reproductive functions such as infertility or infertility, damage to liver and kidney function. This research was conducted to determine the use of Rhodamine B dye in cotton sugar in Pasuruan Regency. The cotton sugar used as the sample was taken from 3 different places, namely Markets (sample A), Town Square (sample B) and Store (sample C) representing the Pasuruan district. Analysis of cotton sugar was carried out by the color drawing method using wool yarn with Thin Layer Chromatography (TLC). The results showed that the three samples were negative and did not contain Rhodamine B red dye, this can be seen from the Rf value which cannot be calculated because on the KLT plate no orange stain was formed under the 366 nm UV lamp. It can be concluded that cotton sugar in Pasuruan Regency is safe for consumption because it does not contain red dye Rhodamin B